Dynamic externalities and structural change in Kenya - Johnston, Bruce F.; Park, Albert (International Food Policy Research Institute, 1995)
Economic development and structural transformation are dynamic processes in which sectoral interactions are numerous and multidirectional. Recent growth literature has noted that many of these effects occur in the form of externalities not captured in a neoclassical accounting of intersectoral resource flows and price adjustments. This work has emphasized, for example, that increasing returns phenomena such as demand externalities (Murphy, Shleifer, and Vishny 1989a) and human capital spillovers (Romer 1986) can play an important role in leading the growth process. The assessment just presented by Bigsten and Collier in chapter 7 takes a primarily static view of agricultural linkages in Kenya. This chapter points out ways in which such a perspective may overlook important aspects of linkage effects and structural transformation in Kenya. The discussion draws heavily on the successful agricultural and rural development experience in Taiwan to illustrate the potential importance of intersectoral linkages and certain dynamic externalities.